OPTIMIZATION OF LOAD IN POWER NETWORKS: LINEAR AND NONLINEAR PROGRAMMING METHODS - Akhmedova Nargiza, (INTERNATIONAL JOURNAL OF SCIENCE-INNOVATIVE RESEARCH, 2025)
Abstract: The optimization of electrical load distribution within power networks is a fundamental problem in modern energy systems. Efficient load allocation ensures reduced energy loss, stability of power systems, and economical operation of generation units. This paper explores the application of linear and nonlinear programming methods to optimize load flow and minimize operational costs in electrical grids. The study compares mathematical models, discusses algorithmic approaches such as the simplex method and gradient-based optimization, and highlights their advantages and limitations in real-world power network operations. The integration of optimization algorithms with modern digital technologies, including smart grids and artificial intelligence, is also analyzed as a key step toward sustainable energy management.